Study of marine microorganism metabolites: new resources for bioactive natural products - Barzkar, Noora; Sukhikh, Stanislav; Babich, Olga (Frontiers in Microbiology, 2024)
The marine environment has remained a source of novel biological molecules with diversified applications. The ecological and biological diversity, along with a unique physical environment, have provided the evolutionary advantage to the plant, animals and microbial species thriving in the marine ecosystem. In light of the fact that marine microorganisms frequently interact symbiotically or mutualistically with higher species including corals, fish, sponges, and algae, this paper intends to examine the potential of marine microorganisms as a niche for marine bacteria. This review aims to analyze and summarize modern literature data on the biotechnological potential of marine fungi and bacteria as producers of a wide range of practically valuable products (surfactants, glyco-and lipopeptides, exopolysaccharides, enzymes, and metabolites with different biological activities: antimicrobial, antitumor, and cytotoxic). Hence, the study on bioactive secondary metabolites from marine microorganisms is the need of the hour. The scientific novelty of the study lies in the fact that for the first time, the data on new resources for obtaining biologically active natural products — metabolites of marine bacteria and fungi — were generalized. The review investigates the various kinds of natural products derived from marine microorganisms, specifically focusing on marine bacteria and fungi as a valuable source for new natural products. It provides a summary of the data regarding the antibacterial, antimalarial, anticarcinogenic, antibiofilm, and anti-inflammatory effects demonstrated by marine microorganisms. There is currently a great need for scientific and applied research on bioactive secondary metabolites of marine microorganisms from the standpoint of human and animal health.